The environmental significance of the dialectic of Enlightenment - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2010)
The title of this paper relates directly to the celebrated work of Max Horkheimer and Theodor W. Adorno: Dialektik der Aufklärung. Philosophische Fragmente. It shows as dialectical because of the ideas associated with engaging the rational mastery of the world from the degeneration of the practical ideas in increasingly sophisticated forms of man's dominion over man. Ecological interpretation of such understanding of the dialectic of Enlightenment gives it a modern expression in the sense that it points to one of the most pressing contemporary problems, born of the mythical inspiration functioning of enlightened reason, and today, in the name of being a man claiming to be his task to demythologize reality. Broadly speaking, in the name of human freedom the idea is to overcome the enlightenment tradition of freedom or its’ degeneration in more subtle forms of practical denial. This study follows this line of reasoning and expresses the conviction that today appears to illustrate the dialectic of enlightenment in environmental and bioethical issues.